Preparation method and application of nanocellulose flexible aerogel

By adding conductive carbon particles to the nanocellulose/conductive carbon particle suspension and performing ultrasonic dispersion, combining in situ oxidation polymerization to form a "core-shell" structure, the problem of mechanical deformation and easy rupture of traditional supercapacitors is solved, and a problem of mechanical deformation and cracking of traditional supercapacitors was prepared with Nanocellulose flexible aerogel with high mechanical flexibility and electrochemical activity, suitable for supercapacitor electrode materials.

CN119391041APending Publication Date: 2025-02-07XINZHOU TEACHERS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411504479.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-26
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional supercapacitors are prone to rupture when mechanically deformed, unable to meet the flexibility needs of wearable electronic devices, and finding the right electrode material has become a key issue.

Method used

Nanocellulose is used as the matrix substance, and nanocellulose/conductive carbon particles are added to the nanocellulose/conductive carbon particles suspension and ultrasonic dispersion is performed to form a nanocellulose/conductive carbon particle hybrid. Then, in-situ oxidation polymer is used to polymerize the conductive polymer outside the aerogel framework to form a "core-shell" structure, and finally make a flexible aerogel by low temperature freeze-drying.

Benefits of technology

The prepared nanocellulose flexible aerogel has good mechanical flexibility and electrochemical activity, and is suitable as an ideal electrode material for supercapacitors, improving capacitance performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391041A_ABST
    Figure CN119391041A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of nano-crystalline cellulose flexible aerogel, nano-crystalline cellulose is used as a matrix substance to prepare nano-crystalline cellulose based conductive aerogel, and the nano-crystalline cellulose is also used as a dispersing agent of a conductive carbon material to assist the conductive carbon material to be uniformly dispersed in water; then polymerizing a layer of conductive polymer outside the nanocellulose-based conductive aerogel by using an in-situ oxidative polymerization method to form a core-shell structure, and finally freeze-drying at low temperature to prepare the nanocellulose flexible aerogel. The nanocellulose flexible aerogel prepared by the method has a three-dimensional network structure inside, is low in density and good in flexibility, has good electric conduction and electricity storage functions, and has application value in the fields of supercapacitors and sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass material conductive energy storage, and specifically relates to a preparation method of a nanocellulose flexible aerogel and application thereof. Background Art

[0002] In order to better adapt to the development needs of personal wearable electronic devices, small energy storage devices with mechanical flexibility have attracted more and more attention, and supercapacitors are one of the research hotspots. Supercapacitors are a new type of energy storage device that combines the high power of double-layer capacitors and the high energy of traditional batteries. However, traditional supercapacitors are easily broken by various mechanical deformations and cannot meet the flexibility requirements of wearable electronic devices. Therefore, wearable energy storage devices need to have the characteristics of flexibility, and finding suitable electrode materials has become a key point.

[0003] Ideal electrode materials should have the characteristics of low resistance required for charge transfer, good electrochemical stability, good mechanical flexibility between substrate and active material, high specific surface area, pore size that can promote ion diffusion, micro-nanostructure distribution, simple preparation, etc. Therefore, the selection of appropriate substrate materials, nano-sizing of electrode materials, and improving the dispersibility of carbon materials are the key to improving the mechanical flexibility, capacitance performance and electrochemical activity of electrode materials, and are also the biggest challenge faced in the application of energy storage. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a nanocellulose flexible aerogel and its application in view of the deficiencies of the above-mentioned prior art. The present invention uses nanocellulose (CNFs) as a matrix material and as a dispersant for conductive carbon materials to assist the conductive carbon materials to be uniformly dispersed in water to form a CNF / carbon material hybrid, and then utilizes an in-situ oxidative polymerization method to polymerize a layer of conductive polymer outside the CNF / carbon material hybrid skeleton to form a "core-shell" structure, and finally freeze-drying at low temperature to form a flexible aerogel. The nanocellulose flexible aerogel prepared by the present invention has good mechanical flexibility and electrochemical activity, and is an ideal supercapacitor electrode material.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0006] A method for preparing a nanocellulose flexible aerogel comprises the following steps:

[0007] S1. Preparation of Nanocellulose-based Conductive Aerogel

[0008] S101, adding conductive carbon particles to the nanocellulose suspension, stirring for 30 to 60 minutes, and then uniformly dispersing by ultrasonication to obtain a nanocellulose / conductive carbon particle suspension;

[0009] S102, heating the nanocellulose / conductive carbon particle suspension obtained in S1 in a water bath to evaporate the solvent, adjusting the concentration to 0.1-1.0%, then freezing it with liquid nitrogen, and performing vacuum freeze drying to obtain a nanocellulose-based conductive aerogel;

[0010] S2. Aerogel functionalization

[0011] S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks, and then pressing them onto a nickel foam sheet of the same size to form an aerogel film; welding the nickel foam sheet and the copper wire of the aerogel film, and covering the exposed metal part with an insulating material to form an insulating layer, thereby obtaining a conductive aerogel film;

[0012] S202, using a three-electrode system, with the conductive aerogel film obtained in S201 as a working electrode, a platinum electrode as a counter electrode, and Ag / AgCl as a reference electrode, adding a conductive polymer monomer to an acidic solution as an electrolyte, and performing electrochemical polymerization using cyclic voltammetry, until a conductive polymer visible to the naked eye is generated on the surface of the conductive aerogel film, stopping the reaction, and obtaining a nanocellulose-conductive carbon particle@polymer composite;

[0013] S203, soaking the nanocellulose-conductive carbon particles@polymer composite obtained in S202 in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then performing vacuum freeze-drying to obtain the nanocellulose flexible aerogel.

[0014] Preferably, the concentration of the nanocellulose suspension in S101 is 0.5wt%; the conductive carbon particles include carbon black, carbon nanotubes, graphite powder, and graphene; and the mass ratio of the nanocellulose to the conductive carbon particles is 1:0.1 to 1:1.

[0015] Preferably, the power of the ultrasonic dispersion in S101 is 200-600 W, and the time is 10-30 min.

[0016] Preferably, the vacuum freeze drying in S102 is carried out at a temperature of -200 to -300°C, a pressure of 1 to 10 Pa, and a time of 12 to 36 hours.

[0017] Preferably, the pressure of pressing the aerogel onto the nickel foam sheet in S201 is 1-10 MPa.

[0018] Preferably, the insulating material in S201 is melted paraffin or melted polyethylene.

[0019] Preferably, the acidic solution in S202 includes sulfuric acid, hydrochloric acid, and phytic acid solution, with a concentration of 5 mol·L -1; The conductive polymer monomers include aniline, pyrrole, and thiophene; the ratio of the acidic solution to the conductive polymer monomer is 250mL:0.25mol.

[0020] Preferably, the scanning voltage range of the electrochemical polymerization in S202 is -0.2 to 0.8 V, and the scanning rate is 60 to 100 mV·s -1 , the number of cycles is 100 to 300.

[0021] Preferably, the vacuum freeze drying in S203 is carried out at a temperature of -200 to -300°C, a pressure of 1 to 10 Pa, and a time of 12 to 24 hours.

[0022] The present invention also provides an application of the nanocellulose flexible aerogel, and the nanocellulose flexible aerogel is used as a supercapacitor electrode material.

[0023] The present invention has the following significant technical effects:

[0024] 1. The present invention provides a method for preparing a nanocellulose flexible aerogel, wherein nanocellulose is used as a matrix material to prepare a nanocellulose-based conductive aerogel, and nanocellulose is also used as a dispersant for a conductive carbon material to assist the conductive carbon material to be uniformly dispersed in water; then, a layer of conductive polymer is polymerized on the outside of the nanocellulose-based conductive aerogel by an in-situ oxidative polymerization method to form a "core-shell" structure, and finally, the nanocellulose flexible aerogel is prepared by low-temperature freeze-drying.

[0025] 2. The present invention uses nanocellulose as the matrix material and adopts freeze-drying method to prepare nanocellulose-based conductive aerogel, which not only has the inherent low density and porosity of aerogel, but also makes the aerogel flexible. Conductive carbon particles are directly mixed with nanocellulose suspension, and ultrasonic dispersion method is adopted, with nanocellulose as dispersant to assist the conductive carbon particles to achieve uniform dispersion in water. The process is simple and the dispersion effect is good. The conductive polymer is directly polymerized on the fiber surface of the conductive aerogel film by electrochemical in-situ oxidative polymerization method. The preparation process is simple and efficient, and finally a nanocellulose-conductive carbon particle@polymer composite aerogel with a "core-shell" structure is obtained, and the particle size distribution is uniform.

[0026] 3. In the present invention, nanocellulose, conductive carbon particles and conductive polymers are combined with each other in a reasonable manner. The flexible aerogel prepared by low-temperature freeze-drying process has the characteristics of many pores, large specific surface area, low density and high specific capacitance. The nanocellulose flexible aerogel prepared by the present invention also has high mechanical flexibility and good stability, and is an ideal supercapacitor electrode material.

[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a real photo of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel of Example 1.

[0029] Figure 2 This is a scanning electron microscope image of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel of Example 1.

[0030] Figure 3 1 is a graph showing the specific surface area and pore size distribution of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel in Example 1 and the multi-walled carbon nanotube@polyaniline composite in Comparative Example 1.

[0031] Figure 4 These are the cyclic voltammograms and constant current charge-discharge diagrams of the nanocellulose / single-walled carbon nanotube@polyaniline composite aerogel in Example 2.

[0032] Figure 5 This is a scanning electron microscope image of the nanocellulose / carbon black@polypyrrole composite aerogel of Example 3.

[0033] Figure 6 This is a test diagram of the electrochemical performance of the flexible aerogel assembled into a supercapacitor in Example 5.

[0034] Figure 7 These are the test results of flexibility and specific capacitance of the flexible aerogel assembled into a supercapacitor in Example 5. DETAILED DESCRIPTION

[0035] Example 1

[0036] This embodiment is a method for preparing a nanocellulose flexible aerogel, comprising the following steps:

[0037] S1. Preparation of Nanocellulose-based Conductive Aerogel

[0038] S101, adding multi-walled carbon nanotubes to 500 mL of a nanocellulose suspension having a concentration of 0.5 wt %, wherein the mass ratio of nanocellulose to multi-walled carbon nanotubes is 1:0.5, mechanically stirring for 30 min, and then using an ultrasonic pulverizer to ultrasonically disperse for 10 min at a power of 200 W to obtain a nanocellulose / conductive carbon particle suspension;

[0039] S102, transferring the nanocellulose / conductive carbon particle suspension obtained in S1 to a beaker, heating with stirring in a water bath to evaporate the solvent of the suspension to make the concentration of the nanocellulose / conductive carbon particles reach 0.5%, pouring into a stainless steel disc mold with a diameter of 20 cm and a depth of 5 cm, using liquid nitrogen to rapidly freeze the suspension, and then placing it in a freeze dryer, freeze-drying at -200°C and 5Pa for 24 hours to obtain a nanocellulose-based conductive aerogel;

[0040] S2. Aerogel functionalization

[0041] S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks of 5 cm×5 cm×1 cm, placing the blocks on a 5 cm×5 cm nickel foam sheet, and pressing the aerogel on the nickel foam sheet at a pressure of 1 MPa to form an aerogel film; welding the nickel foam sheet and the copper wire, and covering the exposed metal part with melted paraffin to form an insulating layer, thereby obtaining a conductive aerogel film;

[0042] S202, using a three-electrode system, the conductive aerogel film obtained in S201 was used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. -1 0.25 mol aniline monomer was added to the phytic acid solution as the electrolyte, and electrochemical polymerization was performed using the CV program (cyclic voltammetry) in an electrochemical workstation with a voltage range of -0.2 to 0.8 V and a scan rate of 60 mV·s -1 After 100 cycles, dark green polyaniline was generated on the fiber surface of the conductive aerogel film. The reaction was stopped to obtain a nanocellulose-multi-walled carbon nanotube@polyaniline composite with a "core-shell" structure.

[0043] S203, immersing the nanocellulose-multi-walled carbon nanotube@polyaniline composite in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then freeze-drying it in a vacuum freeze dryer at -200°C and 5Pa for 12 hours to obtain the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel, i.e., nanocellulose flexible aerogel.

[0044] Comparative Example 1

[0045] The preparation method of multi-walled carbon nanotube@polyaniline composite is as follows:

[0046] A three-electrode system was used, with multi-walled carbon nanotubes as the working electrode, platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. -10.25 mol aniline monomer was added to the phytic acid solution as the electrolyte, and electrochemical polymerization was performed using the CV program in the electrochemical workstation with a voltage range of -0.2 to 0.8 V and a scan rate of 60 mV·s -1 After 100 cycles, dark green polyaniline was generated on the surface of the multi-walled carbon nanotubes. The reaction was stopped to obtain a multi-walled carbon nanotube@polyaniline composite.

[0047] Figure 1 This is a photo of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel of Example 1. A piece of aerogel with a size of 5 cm×5 cm×1 cm has a mass of 0.16 g and a density of 6.4 mg·cm -3 , can be supported by a feather, intuitively demonstrating the low-density characteristics of aerogels.

[0048] Figure 2 This is a scanning electron microscope image of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel prepared in Example 1. The interior of the aerogel is a multi-level pore structure, including micron-scale channels and nano-scale mesopores, and a nano-scale microporous structure is formed between the particles. In the figure, a large amount of polyaniline with a diameter of about 200nm, as well as filamentous nanocellulose and multi-walled carbon nanotubes can be seen, and polyaniline is successfully attached to the surface of nanocellulose and multi-walled carbon nanotubes to form tumor-like protrusions, forming a reasonable "core-shell" structure between the three.

[0049] Figure 3 a is the specific surface area test result of the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel (CC@P-2) of Example 1 and the multi-walled carbon nanotube@polyaniline composite (C@P) of Comparative Example 1. 2 The adsorption-desorption curves show that the adsorption amount increases slowly in the range of P / P0=0.05-0.8. 2 The molecules are adsorbed on the inner surface of the mesopores in a monolayer to multilayer manner; the adsorption amount increases suddenly in the range of P / P0=0.8-1.0, the desorption isotherm does not overlap with the adsorption isotherm, and the desorption isotherm is above the adsorption isotherm. The existence of the hysteresis loop indicates that the material accumulates to form a mesoporous structure, indicating that the pore structure in the nanocellulose-multi-walled carbon nanotube@polyaniline composite aerogel material is uniformly distributed. The specific surface areas of the multi-walled carbon nanotube@polyaniline composite (C@P) of Comparative Example 1 and the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel (CC@P-2) of Example 1 are calculated using the Brunauer-Emmett-Teller (BET) method to be 68.1 m 2 ·g -1 and 121.4m 2 ·g -1. It shows that the specific surface area increases significantly after the introduction of nanocellulose, which is due to the three-dimensional skeleton of nanofibers supporting carbon nanotubes and polyaniline to form a reasonable microstructure inside the composite aerogel, thereby forming a large number of pores to increase the specific surface area of ​​the material. Figure 3 b is the pore size distribution diagram calculated from the desorption branch of the isotherm using the Barrett-Joyner-Halenda (BJH) equation. The total pore volumes of the multi-walled carbon nanotube@polyaniline composite (C@P) of Comparative Example 1 and the nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel (CC@P-2) of Example 1 are 0.39 cm 3 ·g -1 and 0.413cm 3 ·g -1 . The average diameter of the adsorption pores of multi-walled carbon nanotubes @ polyaniline is 18.6nm, and the pore size distribution range is wide, mainly between 20-60nm, which belongs to mesopores and macropores. The average diameter of the adsorption pores of nanocellulose-multi-walled carbon nanotubes @ polyaniline is 14.2nm, and the pore size distribution range is relatively concentrated, mainly between 10-20nm, and there are also some micropores smaller than 2nm, and there are no macropores larger than 50nm. This shows that the introduction of nanocellulose makes the internal structure of the composite aerogel more uniform, so that the multi-walled carbon nanotubes and polyaniline are fully dispersed, and a small pore and mesopore structure is constructed. The liquid electrolyte can penetrate into the aerogel structure through the interconnected mesopores, and provide a pathway for effective electron transport throughout the porous electrode, maximizing the contact area between the active material and the electrolyte, and improving the mobility of the redox dipole. The small pores can act as charge storage sites to increase the capacitance. Polyaniline is coated on the outside of nanocellulose-multi-walled carbon nanotubes to form a "core-shell" structure composite. The fiber network of nanocellulose-multi-walled carbon nanotubes is intertwined to form a porous structure and a high specific surface area, which is beneficial to the transmission and diffusion of electrolyte ions.

[0050] Example 2

[0051] This embodiment is a method for preparing a nanocellulose flexible aerogel, comprising the following steps:

[0052] S1. Preparation of Nanocellulose-based Conductive Aerogel

[0053] S101, adding single-walled carbon nanotubes to 500 mL of a nanocellulose suspension having a concentration of 0.5 wt %, wherein the mass ratio of nanocellulose to single-walled carbon nanotubes is 1:0.1, mechanically stirring for 30 min, and then using an ultrasonic pulverizer to ultrasonically disperse for 30 min at a power of 600 W to obtain a nanocellulose / conductive carbon particle suspension;

[0054] S102, transferring the nanocellulose / conductive carbon particle suspension obtained in S1 to a beaker, heating with stirring in a water bath to evaporate the solvent of the suspension to make the concentration of the nanocellulose / conductive carbon particles reach 0.1%, pouring into a stainless steel disc mold with a diameter of 20 cm and a depth of 5 cm, using liquid nitrogen to rapidly freeze the suspension, and then placing it in a freeze dryer, freeze-drying at -300°C and 1Pa for 36 hours to obtain a nanocellulose-based conductive aerogel;

[0055] S2. Aerogel functionalization

[0056] S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks of 5 cm×5 cm×1 cm, placing the blocks on a 5 cm×5 cm nickel foam sheet, and pressing the aerogel on the nickel foam sheet at a pressure of 5 MPa to form an aerogel film; welding the nickel foam sheet and the copper wire, and covering the exposed metal part with melted paraffin to form an insulating layer, thereby obtaining a conductive aerogel film;

[0057] S202, using a three-electrode system, the conductive aerogel film obtained in S201 was used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. -1 0.25 mol of aniline monomer was added to the hydrochloric acid solution as the electrolyte, and electrochemical polymerization was performed using the CV program (cyclic voltammetry) in the electrochemical workstation with a voltage range of -0.2 to 0.8 V and a scan rate of 80 mV·s -1 After 200 cycles, dark green polyaniline was generated on the fiber surface of the conductive aerogel film. The reaction was stopped to obtain a nanocellulose-single-walled carbon nanotube@polyaniline composite with a "core-shell" structure.

[0058] S203, immersing the nanocellulose-single-walled carbon nanotube@polyaniline composite in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then freeze-drying it in a vacuum freeze dryer at -300°C and 1Pa for 18 hours to obtain the nanocellulose-single-walled carbon nanotube@polyaniline composite aerogel, i.e., nanocellulose flexible aerogel.

[0059] Figure 4 The cyclic voltammetry (a) and constant current charge-discharge (b) curves of the nanocellulose-single-walled carbon nanotube@polyaniline composite aerogel electrode of this embodiment are shown in Figure 1. In the test, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol·L - 1 H 2 SO 4 As electrolyte, the scan rate was 40 mV·s -1, the voltage range is -0.2-0.8V. The redox peaks of the cyclic voltammetry (CV) curve at 0V and 0.4V are derived from the transformation of PANI from a fully reduced all-benzene structure to a partially oxidized benzo-quinone coexistence structure, indicating that the composite aerogel electrode has pseudocapacitive characteristics. The constant current charge-discharge (G-CD) curve shows that the electrode has stable charge and discharge performance, and the charge transfer resistance inside the composite electrode material is small. From the CV and G-CD characterization results, it can be seen that nanocellulose, carbon nanotubes and polyaniline are combined to form a multi-level network complex with a "core-shell" structure. The mass specific capacitance of the electrode was calculated based on the G-CD curve, and it was obtained at a current density of 0.4A g -1 , 0.8A g -1 , 1.2A g -1 , 1.6Ag -1 and 2.0A g -1 When the mass specific capacitance of the electrode is 224.2F g -1 , 197.2F g -1 , 182.4F g -1 , 172.4F g -1 and 166.1F g -1 ; At a current density of 0.4A g -1 When the specific capacitance is 224.2F g -1 .

[0060] Example 3

[0061] This embodiment is a method for preparing a nanocellulose flexible aerogel, comprising the following steps:

[0062] S1. Preparation of Nanocellulose-based Conductive Aerogel

[0063] S101, adding carbon black powder to 500 mL of a nanocellulose suspension having a concentration of 0.5 wt %, wherein the mass ratio of nanocellulose to carbon black powder is 1:1, mechanically stirring for 60 min, and then using an ultrasonic pulverizer to ultrasonically disperse for 20 min at a power of 400 W to obtain a nanocellulose / conductive carbon particle suspension;

[0064] S102, transferring the nanocellulose / conductive carbon particle suspension obtained in S1 into a beaker, heating with stirring in a water bath to evaporate the solvent of the suspension to make the concentration of the nanocellulose / conductive carbon particles reach 1.0%, pouring into a stainless steel disc mold with a diameter of 20 cm and a depth of 5 cm, using liquid nitrogen to rapidly freeze the suspension, and then placing it in a freeze dryer, freeze-drying it at -200°C and 10Pa for 12 hours to obtain a nanocellulose-based conductive aerogel;

[0065] S2. Aerogel functionalization

[0066] S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks of 5 cm×5 cm×1 cm, placing the blocks on a 5 cm×5 cm nickel foam sheet, and pressing the aerogel on the nickel foam sheet at a pressure of 3 MPa to form an aerogel film; welding the nickel foam sheet and the copper wire, and covering the exposed metal part with melted paraffin to form an insulating layer, thereby obtaining a conductive aerogel film;

[0067] S202, using a three-electrode system, the conductive aerogel film obtained in S201 was used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. -1 0.25 mol of pyrrole monomer was added to the sulfuric acid solution as the electrolyte, and electrochemical polymerization was performed using the CV program (cyclic voltammetry) in an electrochemical workstation with a voltage range of -0.2 to 0.8 V and a scan rate of 100 mV·s -1 After 300 cycles, black polypyrrole was generated on the fiber surface of the conductive aerogel film. The reaction was stopped to obtain a nanocellulose-carbon black@polypyrrole composite with a "core-shell" structure.

[0068] S203, immersing the nanocellulose-carbon black@polypyrrole composite in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then freeze-drying it in a vacuum freeze dryer at -200°C and 10Pa for 24 hours to obtain the nanocellulose-carbon black@polypyrrole composite aerogel, i.e., nanocellulose flexible aerogel.

[0069] Figure 5 The middle is a scanning electron microscope image of nanocellulose / carbon black@polypyrrole composite aerogel. In the image, polypyrrole can be seen wrapped on the surface of carbon black particles to form a spherical shape with a diameter of about 100nm. At the same time, it is attached to the surface of nanocellulose and arranged along its axial direction, indicating that polypyrrole is successfully polymerized on the surface of nanocellulose / carbon black to form a "core-shell" structure and attached to the cellulose skeleton network.

[0070] Example 4

[0071] This embodiment is a method for preparing a nanocellulose flexible aerogel, comprising the following steps:

[0072] S1. Preparation of Nanocellulose-based Conductive Aerogel

[0073] S101, adding multilayer graphene to 500 mL of a nanocellulose suspension having a concentration of 0.5 wt %, wherein the mass ratio of nanocellulose to multilayer graphene is 1:0.2, mechanically stirring for 50 min, and then using an ultrasonic pulverizer to ultrasonically disperse for 10 min at a power of 600 W to obtain a nanocellulose / conductive carbon particle suspension;

[0074] S102, transferring the nanocellulose / conductive carbon particle suspension obtained in S1 to a beaker, heating with stirring in a water bath to evaporate the solvent of the suspension to make the concentration of the nanocellulose / conductive carbon particles reach 0.2%, pouring into a stainless steel disc mold with a diameter of 20 cm and a depth of 5 cm, using liquid nitrogen to rapidly freeze the suspension, and then placing it in a freeze dryer, freeze-drying at -300°C and 5 Pa for 36 hours to obtain a nanocellulose-based conductive aerogel;

[0075] S2. Aerogel functionalization

[0076] S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks of 5 cm×5 cm×1 cm, placing the blocks on a 5 cm×5 cm nickel foam sheet, and pressing the aerogel on the nickel foam sheet at a pressure of 10 MPa to form an aerogel film; welding the nickel foam sheet and the copper wire, and covering the exposed metal part with melted polyethylene to form an insulating layer, thereby obtaining a conductive aerogel film;

[0077] S202, using a three-electrode system, the conductive aerogel film obtained in S201 was used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. -1 0.25 mol of thiophene monomer was added to the sulfuric acid solution as the electrolyte, and electrochemical polymerization was performed using the CV program (cyclic voltammetry) in an electrochemical workstation with a voltage range of -0.2 to 0.8 V and a scan rate of 100 mV·s -1 After 200 cycles, black polythiophene was generated on the fiber surface of the conductive aerogel film, and the reaction was stopped to obtain a nanocellulose-multilayer graphene@polythiophene composite with a "core-shell" structure;

[0078] S203, immersing the nanocellulose-multilayer graphene@polythiophene composite in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then freeze-drying it in a vacuum freeze dryer at -300°C and 5Pa for 24 hours to obtain a nanocellulose-multilayer graphene@polythiophene composite aerogel, i.e., a nanocellulose flexible aerogel.

[0079] Example 5

[0080] This example is a study on the performance of nanocellulose flexible aerogel in supercapacitor applications.

[0081] The nanocellulose / multi-walled carbon nanotube@polyaniline composite aerogel prepared in Example 1 was used as an electrode, and polyvinyl alcohol (PVA) / H 2 SO 4As gel electrolyte and nanocellulose (CNF) / polyvinyl alcohol-borate (PVAB) hydrogel matrix were assembled into solid-state flexible supercapacitors, such as the model Figure 6 As shown in a, the assembly method is: PVA / H 2 SO 4 The gel electrolyte wraps the composite aerogel electrode and is then arranged in a finger-like cross pattern on the surface of the CNF / PVAB hydrogel matrix. As water dissipates, the PVA gel electrolyte gradually loses its fluidity and can completely fuse with the PVAB hydrogel as the matrix to form an integrated device.

[0082] Figure 6 b is the cyclic voltammetry (CV) curve of the supercapacitor at different scan rates. As the scan rate increases, the peak current increases, but the shape of the CV curve remains consistent, indicating that the capacitor has excellent fast current response and stable charge and discharge performance. The existence of the redox peak proves that the supercapacitor has typical pseudocapacitive characteristics and can effectively improve the specific capacitance. The pseudocapacitance mainly comes from the transformation of the polyaniline component in the aerogel electrode from the fully reduced all-benzene structure to the partially oxidized benzo-quinone coexistence structure. Among them, the carbon nanotubes with excellent conductivity can significantly improve the conductivity of the composite, act as a fast transfer channel for electrons, and effectively transfer electrons to polyaniline for pseudocapacitive energy storage reaction, while accumulating charges on the surface for double-layer capacitance energy storage. Nanocellulose, as the basic skeleton, provides a three-dimensional network structure, and uses its own hydrophilicity to allow the electrolyte to fully penetrate into the porous structure of the aerogel electrode and fully contact the electroactive materials polyaniline and carbon nanotubes, which is beneficial to the adsorption / desorption of electrolyte ions and improves the efficiency of the electrochemical reaction. Figure 6 c is the constant current charge and discharge curve at different current densities. The curve is a symmetrical triangle structure, indicating good reversibility and efficient charge transfer in the entire capacitor. From the discharge curve, it can be seen that the potential drop is very small, indicating that the equivalent series resistance of the device is small, which is due to the PVA / H 2 SO 4 The higher ionic conductivity of the gel electrolyte and the planar configuration of the device reduce the ion transfer resistance. The lower internal resistance can reduce the useless heat generation during the charge and discharge process, which is very important for energy storage devices. Calculation shows that at 2mA·cm -2 At a current density of , the specific capacitance of the supercapacitor is 722.4mF·cm -2 ; The current density is increased to 10 mA cm -2 When the specific capacitance is still 634.0mF·cm -2, only decreased by 12%, indicating that the capacitor has a high capacitance stability, and its specific capacitance is much higher than that of supercapacitors and some pseudocapacitive material capacitors that rely solely on double-layer capacitance for energy storage. The composite aerogel electrode has a large capacitance because CNFs effectively disperse and load carbon nanotubes. These conductive fibers with a high aspect ratio penetrate the composite aerogel to form an interconnected conductive network, which can effectively improve charge transfer and thus improve the capacitance performance of the composite material. Figure 6 d is the electrochemical impedance spectroscopy (EIS) curve of the supercapacitor, and the inset is the corresponding simulation circuit diagram. The EIS curve shows a typical semicircle in the high-frequency region, and it can be concluded that the equivalent series resistance (Rs) is 13.24Ω and the charge transfer resistance (Rct) is 0.68Ω, which is relatively small. The oblique line in the low-frequency region is called the Warburg impedance, which is closely related to the diffusion of ions between the electrode and the electrolyte interface. The oblique line in the figure is almost perpendicular to the horizontal axis, indicating good capacitance characteristics. The composite capacitance model fitted by the Zview software explains the similarity between the behavior of the supercapacitor and the series-parallel combination of resistance and capacitance. At high frequencies, the capacitance tends to zero because the ions in the electrolyte are located on the outer surface of the electrode instead of entering its interior. At this time, the capacitor is equivalent to a pure resistance device. At low frequencies, the capacitance reaches its maximum because the ions can enter the deep region of the electrode. The region where the capacitance is linearly related to the frequency is the third region, which represents the penetration depth of the electrolyte into the electrode.

[0083] The performance stability of the assembled supercapacitor under bending deformation was studied. The device was bent 180° as a whole, and the capacitors after the 50th, 100th, 150th and 200th bending were measured at 60mV·s -1 Cyclic voltammetry was performed at a scan rate of , and the cyclic voltammetry curve was as follows Figure 7 As shown in a, the curve obtained after multiple bending deformations has no significant change compared with the curve of the initial state, indicating that the capacitance of the capacitor is stable after bending deformation. Figure 7 b, Initial state, supercapacitor at 60mV·s -1 The specific capacitance calculated at a scan rate of 520.0 mF·cm -2 After 50 bending deformations, the specific capacitance dropped to 504.4mF·cm -2 After 100 bending deformations, the specific capacitance dropped to 499.2mF·cm -2 , the specific capacitance is still 494.2mF·cm after 200 bending deformations -2 , the capacitance retention rate reaches 95%. The capacitor shows high flexibility and good stability, and has great application potential in wearable electronic devices. Figure 7The digital photo in c intuitively shows that the capacitor can drive an electronic meter in both straight and bent states, proving that the capacitor has certain practical application value.

[0084] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a nanocellulose flexible aerogel, characterized in that: The following steps are involved: S1. Preparation of Nanocellulose-based Conductive Aerogel S101, adding conductive carbon particles to the nanocellulose suspension, stirring for 30 to 60 minutes, and then uniformly dispersing by ultrasonication to obtain a nanocellulose / conductive carbon particle suspension; S102, heating the nanocellulose / conductive carbon particle suspension obtained in S1 in a water bath to evaporate the solvent, adjusting the concentration to 0.1-1.0%, then freezing it with liquid nitrogen, and performing vacuum freeze drying to obtain a nanocellulose-based conductive aerogel; S2. Aerogel functionalization S201, cutting the nanocellulose-based conductive aerogel obtained in S1 into blocks, and then pressing them onto a nickel foam sheet of the same size to form an aerogel film; welding the nickel foam sheet and the copper wire of the aerogel film, and covering the exposed metal part with an insulating material to form an insulating layer, thereby obtaining a conductive aerogel film; S202, using a three-electrode system, with the conductive aerogel film obtained in S201 as a working electrode, a platinum electrode as a counter electrode, and Ag / AgCl as a reference electrode, adding a conductive polymer monomer to an acidic solution as an electrolyte, and performing electrochemical polymerization using cyclic voltammetry, until a conductive polymer visible to the naked eye is generated on the surface of the conductive aerogel film, stopping the reaction, and obtaining a nanocellulose-conductive carbon particle@polymer composite; S203, soaking the nanocellulose-conductive carbon particles@polymer composite obtained in S202 in flowing deionized water to wash away the unreacted excess ions, then freezing it in liquid nitrogen at low temperature, and then performing vacuum freeze-drying to obtain the nanocellulose flexible aerogel.

2. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: S101 The concentration of the nanocellulose suspension is 0.5wt%; the conductive carbon particles include carbon black, carbon nanotubes, graphite powder, and graphene; the mass ratio of the nanocellulose to the conductive carbon particles is 1:0.1 to 1:

1.

3. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: The power of the ultrasonic dispersion in S101 is 200-600W, and the time is 10-30min.

4. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: The vacuum freeze drying in S102 is carried out at a temperature of -200 to -300°C, a pressure of 1 to 10 Pa, and a time of 12 to 36 hours.

5. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: The pressure of pressing the aerogel onto the nickel foam sheet in S201 is 1 to 10 MPa.

6. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: S201 The insulating material is melted paraffin or melted polyethylene.

7. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: S202 The acidic solution includes sulfuric acid, hydrochloric acid, and phytic acid solution, with a concentration of 5 mol·L -1 ; The conductive polymer monomers include aniline, pyrrole, and thiophene; the ratio of the acidic solution to the conductive polymer monomer is 250mL:0.25mol.

8. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: The scanning voltage range of the electrochemical polymerization in S202 is -0.2 to 0.8 V, and the scanning rate is 60 to 100 mV·s -1 , the number of cycles is 100 to 300.

9. The method for preparing the nanocellulose flexible aerogel according to claim 1, characterized in that: The vacuum freeze drying in S203 is carried out at a temperature of -200 to -300°C, a pressure of 1 to 10 Pa, and a time of 12 to 24 hours.

10. An application of the nanocellulose flexible aerogel according to claim 1, characterized in that: The nanocellulose flexible aerogel is used as a supercapacitor electrode material.